Nietzsche's Revolution - Schotten, C. author. aut Link
XII, 272 p.
Keywords: This book claims Nietzsche as a leftist revolutionary but without overlooking the conservative and retrogressive elements of his political philosophy. The author argues that these two 'halves' of his philosophy help construct a new form of politics for contemporary readers, a possibility of revolution post-Marx.